Farm Production Factors Affecting Malt Sorghum Production among Contracted Sorghum Farmers in Homa Bay County, Kenya - Quinter , Ngode. A.; Elijah , Ng’eno K.; Victoria , Anjichi (African Journal of Education,Science and Technology (AJEST), 2021)
Sorghum is a globally important food security crop with high commercial importance, particularly in arid and semiarid regions. Though its production in Kenya is crucial in ensuring increased agricultural productivity and income, sorghum farmers in Homa Bay County still record low yield. This research was intended to determine the factors affecting production of malt sorghum among contracted sorghum farmers in Homa Bay County, Kenya and a total of 217 East Africa Breweries Limited (EABL) contracted farmers participated. Survey information were analyzed using descriptive statistics and double log Cobb-Douglas production function. Results revealed that the mean age of the contracted malt sorghum farmers was 45 years with 1.5 years of experience and produce on average 2,203kg of malt sorghum per acre per cropping season. On average, 20% of the farmers planted Sila while 49.2% planted Gadam varieties of malt sorghum. Analyzed results revealed a one percent increase in land size would increase malt sorghum yield by 155.4%, while a one percent increase in quantity of seed, pests and disease attack, labor would lead to a decline in malt sorghum yield by 57.2%, 26.8% and 11.4% respectively. To improve malt sorghum productivity, recommendation to the county and the national governments of Kenya is made come up with strategies to address the challenges of seed quantity, pests and diseases and labor. Such strategies may involve the introduction of drones and chemical perch repellants that are neither harmful to sorghum grain nor human beings and farmers should be encouraged to plant simultaneously.